Regeneration of kola trees, Cola nitida (Vent) Schott and Endlicher, by coppicing - Odegbaro, O.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Old kola trees whose production was already very low were cut for regrowth at the beginning, middle and end of the rainy season at various heights, 30, 60 and 120 cm from the ground level, in order to study the regeneration of the trees for the possible use of this method in the rehabilitation of kola. Young shoots were produced on the buds that formed, one, two or three of the shoots were selected and allowed to grow normally while the others were removed.